Operational Risk Assessment Tool for Evaluating Leishmania infantum Introduction and Establishment in the United States through Dog Importation - David R. Marquez; Anne Straily; Keeve Nachman; Douglas E. Norris; Meghan F. Davis; Christine A. Petersen (Emerging Infectious Diseases)
International pet travel and commercial operations have increased animal disease importation risks, including for Leishmania infantum, a deadly parasite of humans and domestic dogs. Collaborating as an interdisciplinary working group, we developed an operational tool for veterinary and public health practitioners to assess and manage L. infantum risk in dogs imported to the United States. Overall risk varies by dog, human, and geographic factors but could be high without proper controls. We determined dog risk management strategies should include application of sand fly insecticides and repellents, sterilization, and treatment. US public health authorities can use a One Health approach to manage L. infantum importation risks via infected dogs.